Randomized Trial of Lactin-V to Prevent Recurrence of Bacterial Vaginosis. Issue 10 (October 2020) - Cohen, Craig R.; Wierzbicki, Michael R.; French, Audrey L.; Morris, Sheldon; Newmann, Sara; Reno, Hilary; Green, Lauri; Miller, Steve; Powell, Jonathan; Parks, Thomas; Hemmerling, Anke
Abstract : (Abstracted from N Engl J Med 2020;382:1906–1915) Worldwide, 15% to 50% of women of reproductive age have bacterial vaginosis (BV) and are treated with an antibiotic agent. Within 3 months after treatment, the infection recurs in 20% to 75% of women.